2020
DOI: 10.1038/s41467-020-19363-y
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: SARS-CoV2-mediated suppression of NRF2-signaling reveals potent antiviral and anti-inflammatory activity of 4-octyl-itaconate and dimethyl fumarate

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…Experimental data show that enhancement of the NRF2-pathway reduces macrophage-mediated alveolar damage and induces the expression of antioxidant genes during influenza [ 26 ]. Moreover, a recent study demonstrated that dimethylfumarate inhibits SARS-CoV-2 replication and the expression of associated inflammatory genes [ 27 ]. Therefore, dimethyl fumarate could have a beneficial anti-inflammatory and cytoprotective action in SARS-CoV-2 infection.…”
Section: Disease-modifyng Therapies and Covid-19mentioning
confidence: 99%
“…Experimental data show that enhancement of the NRF2-pathway reduces macrophage-mediated alveolar damage and induces the expression of antioxidant genes during influenza [ 26 ]. Moreover, a recent study demonstrated that dimethylfumarate inhibits SARS-CoV-2 replication and the expression of associated inflammatory genes [ 27 ]. Therefore, dimethyl fumarate could have a beneficial anti-inflammatory and cytoprotective action in SARS-CoV-2 infection.…”
Section: Disease-modifyng Therapies and Covid-19mentioning
confidence: 99%
“…Komaravelli and Casola [ 170 ] have associated respiratory viral infections with the inhibition of nuclear erythroid factor 2-related factor 2 (Nrf2) and activation of NF-κB, phenomena that incline the balance to inflammation and oxidative damage during these infections [ 170 ]. In a study conducted on lung biopsies from patients with COVID-19, the Nrf2 pathway was found to be suppressed, while pharmacological inductors of Nrf2 have been observed to inhibit SARS-CoV-2 replication and the inflammatory response [ 198 ]. On the other hand, it is known that Nrf2 deficiency increases ACE2 availability, while activation produces the opposite, suggesting that Nrf2 activation in COVID-19 patients could reduce ACE2 availability for entry of SARS-CoV-2 in the cell [ 199 ].…”
Section: Role Of Oxidative Stress and Antioxidant System In Patients With Covid-19mentioning
confidence: 99%
“…IRF3 inhibition has been associated with Nrf2 expression since its silencing is enough to restore IRF3 dimerization and limit the effect of 4-OI. The authors propose the use of DMF and 4-OI as Nrf2 agonists that can be used to inhibit SARS-CoV-2 replication as well as the expression of associated inflammatory genes in patients with COVID-19 [ 198 ].…”
Section: Antioxidants As Neuroprotectors In Patients Infected With Covid-19mentioning
confidence: 99%
“…In previous studies, Nrf2 was under-expressed in human coronavirus HCoV-229E which is associated with the common cold and pulmonary edema [ 87 ]. Interestingly, Nrf2 suppression was also found in the lung biopsies of patients with COVID-19 [ 88 ]. In fact, ACE2 expression is also regulated by Nrf2 pathway, and few studies demonstrated that Nrf2 under-expression increases the availability of ACE2 and that may increase the risk of viral infection [ 89 ].…”
Section: Role Of Covid-19 In Redox Imbalance and Mitochondrial Dysfunctionmentioning
confidence: 99%